2013
DOI: 10.5897/ajb2013.13118
|View full text |Cite
|
Sign up to set email alerts
|

Ginger-supplemented diet ameliorates ammonium nitrate-induced oxidative stress in rats

Abstract: The present study was designed to evaluate the capacity of ginger to repair the oxidative stress induced by ammonium nitrate. 50 male rats were divided into 5 groups; they underwent an oral treatment of ammonium nitrate and/or ginger (N mg/kg body weight + G% in diet) during 30 days. Group I served as control (C); group II (G) received a diet with 2% of ginger; group III (N) received a toxic dose of ammonium nitrate and normal diet; group IV (NG) received a toxic dose of ammonium nitrate and a diet containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Additionally, waste products from protein metabolism that are eliminated by the kidneys, such as blood creatinine, urea, and uric acid concentrations, are usually regarded as indicators of kidney function (Tootian et al, 2012). Accordingly, our results showed a significant increase in blood urea, creatinine, and uric acid levels in response to (Ca(NO 3 ) 2 4H 2 O)toxicity, similar to those previously reported (Messaadia et al, 2013).The increased blood urea, uric acid, and creatinine levels suggested impaired renal function as evidenced by changes in reabsorption threshold, renal blood flow, and glomerular filtration. The results of the present work indicated that (Ca (NO 3 ) 2 4H 2 O) induces histopathological alterations in the liver characterized by venous congestion, mononuclear cell infiltration, cytoplasmic vacuolation of hepatocytes, and fatty degeneration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, waste products from protein metabolism that are eliminated by the kidneys, such as blood creatinine, urea, and uric acid concentrations, are usually regarded as indicators of kidney function (Tootian et al, 2012). Accordingly, our results showed a significant increase in blood urea, creatinine, and uric acid levels in response to (Ca(NO 3 ) 2 4H 2 O)toxicity, similar to those previously reported (Messaadia et al, 2013).The increased blood urea, uric acid, and creatinine levels suggested impaired renal function as evidenced by changes in reabsorption threshold, renal blood flow, and glomerular filtration. The results of the present work indicated that (Ca (NO 3 ) 2 4H 2 O) induces histopathological alterations in the liver characterized by venous congestion, mononuclear cell infiltration, cytoplasmic vacuolation of hepatocytes, and fatty degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, increased levels of ALT and AST in the blood indicate their increased release in blood following hepatocyte necrosis leading to liver impaired function (Krim et al,2013). As previously reported, the concentration of transaminases (AST, ALT) may become high in ammonium nitrate (Messaadia et al, 2013) or sodium nitrate treated rats (Delgadoa et al,2018). In this study, calcium nitrates induced a marked decrease in blood total protein levels.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation